The Dynamics of Islamic Finance in Kazakhstan: Exploring Opportunities and Addressing Challenges - Syed Muhammad Abdul Rehman Shah; Zhainar Zhabatayeva; Memoona Ansar (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2025)
Introduction: This paper explores the burgeoning field of Islamic finance in Kazakhstan, highlighting the opportunities and challenges that lie ahead. Islamic finance, which adheres to Sharia law, provides a distinct alternative to conventional banking systems. As Kazakhstan seeks to diversify its financial sector and attract investments from Muslim-majority countries, understanding the dynamics of Islamic finance becomes crucial. This study examines the legislative framework, market potential, key players, and the socio-economic implications of Islamic finance in Kazakhstan. The case study of existing Islamic banks is given, and their financial performance is examined. Methods: This research employed a qualitative approach, incorporating a literature review and descriptive-exploratory analysis. Primary data were obtained from academic literature, official reports from international financial institutions, Kazakh government regulations, and publications related to the development of Islamic finance in Central Asia. Data analysis techniques included reduction, categorization, and thematic interpretation to identify the dynamics, opportunities, and challenges associated with the implementation of Islamic finance in Kazakhstan. This approach was chosen to provide an in-depth understanding of the actual conditions and prospects of Islamic finance, while also generating strategic recommendations for the development of the industry at the national and regional levels. Results: The research paper also highlights the obstacles faced by the Islamic finance sector and the potential for expanding its implementation. Conclusion and suggestion: The paper further recommends solutions for integrating Islamic finance into Kazakhstan’s economy.